Toksisitas Campuran Ekstrak Daun Sirsak (Annona muricata) dan Daun Pepaya (Carica papaya) terhadap Larva Nyamuk Aedes aegypti dan Pemanfaatannya sebagai Leaflet - Novita Amalia (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Dengue fever is a major public health problem in tropical regions, including Indonesia, due to the widespread presence of Aedes aegypti as its main vector. The continuous use of chemical larvicides may lead to environmental pollution and insect resistance, highlighting the need for safer alternatives. This study aimed to determine the toxicity (LC50) pf a mixture of soursop leaf extract (Annona muricata) and papaya leaf (Carica papaya) against Aedes aegypti larvae within 24 hours and to evaluate the feasibility of a leaflet developed as an educational product. This study use a laboratory experimental design involving third to early fourth instar larvae of Aedes aegypti. The mixture extract were prepared at a ratio of 2:3 and tested at concentrations of 50, 100, 200, 400 ppm. Positive and negative controls were included. Each treatment was replicated four times using 20 larvae per replicate. Larval mortality was recorded after 24 hours, and the LC50 value was analyzed using probit analysis with SPSS software. A leaflet was then developed based on the research results and evaluated by material experts, media experts, and community representatives. The results showed that the LC50 value of the mixed extracts was 262.838 ppm, indicating toxic activity and effectiveness as a natural larvicide. The leaflet validation produced an average score of 90.88%, categorized as very feasible. In conclusion, the mixture of soursop and papaya leaf extracts has strong potential as an environmentally friendly biolarvicide. In addition, the developed leaflet is suitabelfor use as an educational medium to support community-based dengue vector control efforts.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Aedes aegypti; biolarvaicide; soursop leaf; papaya leaf; leaflet